An Early Date for Acts?: Dispensing with Some Recent Arguments - Glover, Daniel B. (Bulletin for biblical research, 2025)
Several recent and noteworthy studies have advocated for an early dating (ca. 62-64) for Luke’s composition of Acts. This article evaluates each argument offered in favor of an early date in these studies and demonstrates that the assumptions undergirding them are problematic. After demonstrating that none of the arguments for an early date are conclusive, this article puts forward evidence that illustrates the viability of a later date for Acts (ca. 100-130). Finally, this article offers exegetical implications of accepting a later date for Acts, using the conclusion of Acts as a case study.